1963
DOI: 10.1139/o63-078
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Extraction and Distribution Studies of Egg Yolk Lipoproteins

Abstract: I'he three lipoproteins of egg yolk, a-and p-lipovitellin and the low-density fraction (LDF), have been isolated and their lipid compositions determined. a-and p-lipovitellin comprise 22 to 2670 lipid, of which 6 l y O is phospholipid, .35(,% is triglyceride, and 4y0 is cholesterol and its esters. L D F contains about 89(y0 lipid having 27y0 phospholipid, 69y0 triglyceride, and 4y0 cholesterol and cholesterol esters. The phospholipids of the three lipoproteins are similar, i.e., 74'% lecithins, 18% cephalins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Because LDL consists of 86%–89% lipids and 12.5% proteins (Martin et al, 1963), lipids have been the main focus for the study of the protective role of egg yolk (eg, Purdy and Graham, 2004; Ricker et al, 2006). However, besides egg yolk, other additives such as skimmed milk, soybean proteins, and bovine serum albumin (Stoss and Holtz, 1983; Foote et al, 2002) have also been used successfully in sperm cryopreservation as membrane stabilizers.…”
Section: Discussionmentioning
confidence: 99%
“…Because LDL consists of 86%–89% lipids and 12.5% proteins (Martin et al, 1963), lipids have been the main focus for the study of the protective role of egg yolk (eg, Purdy and Graham, 2004; Ricker et al, 2006). However, besides egg yolk, other additives such as skimmed milk, soybean proteins, and bovine serum albumin (Stoss and Holtz, 1983; Foote et al, 2002) have also been used successfully in sperm cryopreservation as membrane stabilizers.…”
Section: Discussionmentioning
confidence: 99%
“…Powrie et al (1963) demonstrated that in crude lipovitellin preparations, proteins form complexes on freezing and thawing. Martin et al (1963) believed that a-and /3-lipovitellin have a structural integrity approaching that of a protein molecule. Burley (1963) suggested that in the lipovitellins, the proteins and lipids are combined in a structure that is flexible enough to accommodate large amounts of certain other substances and that the process of expansion assists aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The egg yolk very low density lipoproteins were prepared from freshly laid eggs and from eggs which had been kept in cold storage for 6 months, using the procedure of Martin et al (1963) as modified by Evans et al (1968). Fresh preparations of the egg yolk very low density lipoproteins were made for each study.…”
Section: Methodsmentioning
confidence: 99%